The Inclusion Principles of Human Embryos in the WOW-Based Time-Lapse System: A Retrospective Cohort Study - Wang, Yuqiong; Wang, Sheng; Qian, Xilin; Kuai, Yanrong; Xu, Yang (Frontiers in Endocrinology, 2021)
A time-lapse system (TLS) with a well-of-the-well (WOW) dish, which allows individual identification and the possibility of autocrine and paracrine signaling between group-cultured embryos, has been widely used in clinic. However, there is a need to re-think the inclusion principles of human embryos in WOW-based TLS, especially for grade IV (G4) embryos, which are considered to potentially have detrimental effects on surrounding embryos. Here, we carried out a single-center, large-cohort, retrospective study, comprising 303 patients undergoing IVF (148 cases) and ICSI (155 cases), with a total of 3282 embryos, to compare embryonic development until the blastocyst stage in the group culture system with or without G4 embryos. Further, LC-MS/MS was used to analyze the G1-G4 embryo secretome to understand the influence of G4 embryos on the group culture microenvironment. We proved that polypronuclear (PPN) embryos positively contribute to the development of the neighboring embryos through secretion of ILIAP, ITI-H4, and keratin. Existence of more than one G4 embryo had a negative effect on the other embryos (p < 0.05). Moreover, G4 embryos were found to secrete KLKB1 and VTDB, which might harm the neighboring embryos. Thus, our study clarified that when embryos are subjected to group culture in WOW-based TLS, the PPN-derived embryos need not be removed, and it is important to ensure that no more than one G4 embryo is present to avoid negative effects on the neighboring embryos.